Relationship between Vocabulary Knowledge and Inferential Reading Comprehension in Junior High Students: English - Tarisya Zulfa; Eva Rahmawati (JOEY: Journal of English Ibrahimy, 2026)
Vocabulary knowledge is an essential component of reading comprehension, particularly inferential comprehension, which requires readers to interpret implicit meaning rather than relying solely on explicitly stated information. For many EFL learners, an insufficient vocabulary base makes inferential comprehension difficult to achieve. Although previous studies have widely confirmed the importance of vocabulary for reading comprehension, limited research has specifically examined how vocabulary knowledge across different word-frequency levels relates to inferential reading comprehension at the junior high school students’ vocabulary knowledge and their inferential reading comprehension using a quantitative correlational design involving 53 eighth-grade students. Vocabulary knowledge was measured using the Updated Vocabulary Levels Test (1000-5000 levels), while inferential reading comprehension was assessed through an inference-based reading test adapted from TOEFL Junior materials. Data were analyzed using descriptive statistics and Spearman’s rho correlation. The results showed that students achieved strong mastery at the 1000-word level (92.5%), with mastery declining and becoming more varied at the 2000-word (62.3%) through 5000-word levels. Inferential reading comprehension yielded a mean score of 57.83, falling into the sufficient category. Spearman’s rho analysis revealed a significant moderate positive correlation between vocabulary knowledge and inferential reading comprehension (r = .488, p = .000), particularly strong at the 1000-word (r = .513) and 2000-word (r = .541) levels. These findings indicate that vocabulary mastery at basic and intermediate levels serves as a primary predictor of inferential reading performance, suggesting that teachers should prioritize structured vocabulary instruction to facilitate students’ transition toward higher-order reading skills.